An Investigation on How University Students’ View Lecturers’ Usage of Speech Acts in ELT context - Mutiara Shasqia; Aulia Anggraini (Utamax : Journal of Ultimate Research and Trends in Education, 2020)
Teachers and lecturers alike understand that they must consciously use a variety of speech acts to force students to follow their instructions and be motivated to learn on their own. This paper reports the findings of a study designed to investigate the notion of the perlocutionary effect of university students in the classroom resulted from lecturers’ illocutionary acts. The acts were then analyzed the illocutionary act of the lecturers’ talk or speech during specific time using Austin’s speech act theory. This present study built its investigation from data collection on both lecturers and university students through interview and field notes. This study manage to reveals that lecturers freely use speech acts of persuading, angering, and commanding. This study believes that illocutionary acts will still have happened in our interaction's life or communication in many-many context including classroom interaction between lecturer-students communication context.